Cancer Therapy Resistance: Choosing Kinase Inhibitors - Carmela Dell'Aversana; Federica Sarno; Rosaria Benedetti; Wouter Leonard Megchelenbrink; Donato Cappetta (MDPI AG, 2024)
Recent advances in comprehending the essential molecular mechanisms that govern cancer signaling have revealed the pivotal involvement of kinases in the development and progression of various cancer types [...]